BlackBerry Curve Made Simple - Trautschold, Martin (Apress, 2012)
In your hands is one of the most capable devices to hit the market in quite some time: the BlackBerry Curve. This Quick Start Guide will help get you and your new Curve up and running in a hurry. You’ll learn all about the buttons, switches, and ports, and how to use the responsive Trackpad to help you get around. Our App Reference Tables introduce you to the apps on your Curve—and serve as a quick way to find out how to accomplish a task.